1994
DOI: 10.2307/2061749
|View full text |Cite
|
Sign up to set email alerts
|

A Theory of the Value of Children

Abstract: This paper uses a non-standard value assumption--uncertainty reduction--to explain parenthood. We begin by reviewing the inadequacies of normative and standard rational choice explanations of shifts in fertility behavior. Then we propose a theory of the value of children based on the uncertainty-reduction assumption. Next we generate a range of hypotheses that follow both from this assumption and from a subsidiary assumption of marital solidarity enhancement. Finally, we explore the extent to which implication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
300
0
22

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 409 publications
(333 citation statements)
references
References 81 publications
11
300
0
22
Order By: Relevance
“…Hoffman and Hoffman (1973), for instance, listed nine dimensions that contribute to determine the value of children: (1) social identity and adulthood status; (2) the expansion of the self, the link to a larger entity, the desire of ''immortality''; (3) morality, religion, altruism, group welfare, norms concerning sexual behaviour, impulsive action, virtues; (4) primary group ties, affection; (5) stimulus, novelty, amusement; (6) realisation, competence, creativity; (7) power, influence, efficacy; (8) social comparison, competition; (9) economic utility. Friedman and colleagues (Friedman et al 1994) criticise the nine-typologies list of Hoffman and Hoffman because of its omni-comprehensiveness. By analysing childbearing decisions in contemporary contexts, where the economic utility of having children is not supposed to play an important role, Friedman and colleagues link the value of children to the capacity of a child to ''reduce uncertainty'' in a potential parent's life.…”
Section: Attitudesmentioning
confidence: 99%
“…Hoffman and Hoffman (1973), for instance, listed nine dimensions that contribute to determine the value of children: (1) social identity and adulthood status; (2) the expansion of the self, the link to a larger entity, the desire of ''immortality''; (3) morality, religion, altruism, group welfare, norms concerning sexual behaviour, impulsive action, virtues; (4) primary group ties, affection; (5) stimulus, novelty, amusement; (6) realisation, competence, creativity; (7) power, influence, efficacy; (8) social comparison, competition; (9) economic utility. Friedman and colleagues (Friedman et al 1994) criticise the nine-typologies list of Hoffman and Hoffman because of its omni-comprehensiveness. By analysing childbearing decisions in contemporary contexts, where the economic utility of having children is not supposed to play an important role, Friedman and colleagues link the value of children to the capacity of a child to ''reduce uncertainty'' in a potential parent's life.…”
Section: Attitudesmentioning
confidence: 99%
“…Research has consistently shown that working women (Rhee, 1973;Ritchey & Stokes, 1974;De Jong & Sell, 1977;Veevers, 1979;Houseknecht, 1987;Heaton et al, 1999) and women in high-status jobs (De Jong & Sell, 1977;Bloom & Pebley, 1982;Callan, 1986;Friedman et al, 1994) are more likely to remain childless than their female counterparts. Associations between employment and childlessness are less well documented for men.…”
Section: Employment Pathwaymentioning
confidence: 99%
“…Becker's microeconomic model; the Easterlin-Crimmins socio-economic model; Friedman et al (1994) uncertainty model; the social capillarity model; Davis's multiphasic model; Coale's model of the three preconditions; transition theory; Lesthaeghe on secular individualism; the newer models on 'social influence' and diffusion. Which is the true model of fertility?…”
Section: Demography Reconsideredmentioning
confidence: 99%